(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The crisis in modern theoretical physics and cosmology has its root in its use, along with theology as a ruling-class tool, since medieval Europe. The Copernican revolution overthrowing the geocentric cosmology of theology led to unprecedented social and scientifi c developments in history.